Does Adjuvant Treatment With Ginkgo Biloba to Statins Have Additional Benefits in Patients With Dyslipidemia? - Fan, Yu; Jin, Xin; Man, Changfeng; Gong, Dandan (Frontiers in Pharmacology, 2018)
Objective: Ginkgo biloba are widely used alone or in combination with other lipid-lowering agents in the treatment of dyslipidemia in China. We conducted this meta-analysis to investigate whether adjuvant treatment with ginkgo biloba leaves to statins has incremental benefits in patients with dyslipidemia. Methods: Potential studies were searched from PubMed, EMBASE, Cochrane Library, China National Knowledge Infrastructure, VIP, and Wanfang database up to October 2017. Only randomized controlled trials (RCTs) comparing the efficacy and safety of ginkgo biloba leaves plus statins versus statins alone in patients with dyslipidemia were included. Results: Eight RCTs involving 664 patients were included. Compared with statins therapy alone, combination of statins and ginkgo biloba leaves therapy achieved greater reductions in triglycerides (mean difference [MD] -0.32 mmol/L; 95% confidence interval [CI] -0.43 to -0.20),total cholesterol (MD -0.61 mmol/L; 95% CI -0.90 to -0.33), or low-density lipoprotein cholesterol (MD -0.32 mmol/L; 95% CI -0.48 to -0.16), and a greater increment in high-density lipoprotein cholesterol(MD 0.26 mmol/L; 95% CI 0.15 to 0.37). Subgroup analyses showed that ginkgo biloba leaves plus simvastatin appeared to achieve a greater reduction in serum levels of triglycerides, total cholesterol, and low-density lipoprotein cholesterol than in combination with atorvastatin therapy. Conclusions: This meta-analysis suggests that adjuvant treatment with ginkgo biloba leaves appears to improve blood lipid parameters than statins therapy alone. More well-designed RCTs are needed to investigate the benefits of the combination of statins and ginkgo biloba leaves.